2021
DOI: 10.1097/tp.0000000000003765
|View full text |Cite
|
Sign up to set email alerts
|

Myeloid and Mesenchymal Stem Cell Therapies for Solid Organ Transplant Tolerance

Abstract: TRANSPLANT TOLERANCE AND TOLEROGENIC CELL TYPESImmunological tolerance is the "holy grail" of transplantation and describes nonreactivity of the recipient's immune system to the nonself, immunogenic donor Review Abstract. Transplantation is now performed globally as a routine procedure. However, the increased demand for donor organs and consequent expansion of donor criteria has created an imperative to maximize the quality of these gains. The goal is to balance preservation of allograft function against patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 216 publications
0
5
0
Order By: Relevance
“…Despite several studies reporting that macrophages accelerate aGVHD, they can be therapeutic depending on the number, properties, and utilization pattern. 46,47 However, it is still unclear how macrophages in SLOs especially in LNs are generated. Recently, Valencia et al have found that FRCs in LNs secrete several factors related to macrophage expansion.…”
Section: Discussionmentioning
confidence: 99%
“…Despite several studies reporting that macrophages accelerate aGVHD, they can be therapeutic depending on the number, properties, and utilization pattern. 46,47 However, it is still unclear how macrophages in SLOs especially in LNs are generated. Recently, Valencia et al have found that FRCs in LNs secrete several factors related to macrophage expansion.…”
Section: Discussionmentioning
confidence: 99%
“…This paper further highlights the need for further -omic studies to identify a consensus gene expression profile, including distinct signaling pathways, that can confirm tolDC function and stability in vivo . Despite the reported safety of tolDC in early-phase human trials ( 17 ), and known efficacy in large animal models ( 76 ), potential variability in clinical grade tolDC preparations remains a concern for translational purposes. The advent of standardized tolDC manufacturing through Focus and Accelerate Cell-based Tolerance-inducing Therapies ( 77 ) aims to minimize variations in approach and is a key step towards a standardized tolDC production for pre-clinical studies and clinical trials.…”
Section: Discussionmentioning
confidence: 99%
“…Although expression appears relatively conserved between species, tissues and disease models ( 2 ), the same standardized characteristics are not yet available for tolDC. Indeed, tolDC used in recent clinical studies did not have uniform methods for generation, phenotype or functional measurements ( 17 ). To date, there is no consensus for “gold-standard” validation of tolerogenic properties, and current methods range from analysis of cell-surface markers to allogeneic T cell stimulation ( 10 ).…”
Section: Introductionmentioning
confidence: 99%
“…Bone marrow mesenchymal stem cells (BMMSCs) have the characteristics of easy access, a high proliferation rate, and low immunogenicity. They play an important role in organ injury repair and transplantation immune regulation [ 4 6 ]. However, the complex pathophysiological environment in the lesion, such as oxidative stress, seriously limits the survival of BMMSCs and reduces the efficacy of BMMSCs transplantation.…”
Section: Introductionmentioning
confidence: 99%